The midwifery-led care model: a continuity of care model in the birth path - Ricchi, Alba; Rossi, Franco; Borgognoni, Patrizia; Bassi, Maria Chiara; Artioli, Giovanna; Foa, Chiara; Neri, Isabella (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the study: The birth path is affected by a fragmentation in the patient care process, creating a discontinuity of this last one. The pregnant woman has to interface with many professionals, both during the pregnancy, the childbirth and the puerperium. However, during the last ten years, there has been an increasing of the pregnancy care operated by the midwife, who is considered to be the operator with the right competences, who can take care of every pregnancy and may avail herself of other professionals’ contributions in order to improve the outcomes of maternal and neonatal health. Aim: To verify whether there are proofs of effectiveness that support the caseload midwifery care model, and if it is possible to apply this model in the birth path in Italy. Methods: A revision of literature has been done using some search engine (Google, Bing) and specific databases (MEDLINE, CINAHL, Embase, Home - ClinicalTrials.gov). There has also been a consultation of the Italian regulations, the national guidelines and the recommendations of WHO. Results: The search string, properly adapted to the three databases, has given the following results: MEDLINE 64 articles, CINAHL 94 articles, Embase 88 articles. From this selection, 14 articles have been extracted: 1 systematic review, 3 controlled random trial, 7 observational studies, 3 qualitative studies. Conclusions: The caseload midwifery care seems to be an effective and reliable organisational/caring method. It responds to the criterions of quality and security, to the needs of women not only during the pregnancy but also during the post-partum phase. For these reasons, it seems very useful also for the birth path in the Italian reality.